Polynomials
Exercise 2.5 Part 10
Question: 9 – Verify:
(i) `x^3 + y^3 = (x + y)(x^2 - xy + y^2)`
Answer: RHS = `(x + y)(x^2 - xy + y^2`
`= x^3 - x^2\y + xy^2 + yx^2 - xy^2 + y^3`
`= x^3 + y^3` = LHS proved
(ii) `x^3 + y^3 = (x - y)(x^2 + xy + y^2)`
Answer: RHS `= (x - y)(x^2 + xy + y^2`
`= x^3 + x^2\y + xy^2 - yx^2 - xy^2 - y^3`
`= x^3 - y^3` = LHS Proved
Question: 10 – Factorise each of the following:
(i) `27y^3 + 125z^3`
Answer: Given; `27y^3 + 125z^3`
`= (3y)^3 + (5z)^3`
Using the identity `x^3 + y^3 = (x + y)(x^2 - xy + y^2)`
We get: `27y^3 + 125z^3`
`= (3y + 5z)[(3y)^2 - 3y\xx5z + (5z)^2]`
`= (3y + 5z)(9y^2 - 15yz + 25z^2)`
(ii) `64m^3 - 343n^3`
Answer: Given; `64m^3 - 343n^3`
`= (4m – 7n)[(4m)^2 + 4m\xx7n + (7n)^2]`
`= (4m – 7n)(16m^2 + 28mn + 49n^2)`
Question: 11 – Factorise:
`27x^3 + y^3 + z^3 - 9xy\z`
Answer: Given; `27^3 + y^3 + z^3 - 9xy\z`
`= (3x)^3 + y^3 + z^3 - 3xx3xy\z`
Using the identity `x^3 + y^3 + z^3 - 3xy\z`
`= (x + y + z)(x^2 + y^2 + z^2 - xy – yz – xz)`
We get: `(3x + y + z)[(3x)^2 + y^2 + z^2 - 3xy – yz – 3xz]`
`= (3x + y + z)(9x^2 + y^2 + z^3 - 3xy – yz – 3xz)`